2020
DOI: 10.30773/pi.2020.0358
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Serotonin 2A Receptor rs6311 Polymorphism with Diurnal Preference in Koreans

Abstract: Objective Evidence for the association between circadian rhythm delay and depression is accumulating. Genetic studies have shown that certain polymorphisms in circadian genes are potential genetic markers of diurnal preference. Along with circadian genes, there is a growing interest in other genetic effects on circadian rhythms. This study evaluated whether the <i>HTR2A</i> rs6311 (-1438C/T) polymorphism is associated with diurnal preference in a Korean population.Methods A total of 510 healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…1067), and the study was conducted in accordance with the Declaration of Helsinki. Other findings related to these participants have been reported previously [12,16,17,[25][26][27].…”
Section: Subjectssupporting
confidence: 84%
See 1 more Smart Citation
“…1067), and the study was conducted in accordance with the Declaration of Helsinki. Other findings related to these participants have been reported previously [12,16,17,[25][26][27].…”
Section: Subjectssupporting
confidence: 84%
“…Circadian genes, such as CLOCK, PER2, PER3, CRY1, ARNTL, and RORa, have been investigated for their association with diurnal preference, but many studies did not find any statistical significance or failed to replicate previous positive finding [12][13][14][15][16]. Yeom et al [17] suggested that HTR2A, a gene encoding one of the serotonin receptors, is associated with diurnal preference. Considering the close relationship between the serotonergic and circadian system, this finding seems to be reasonable and leads to the possibility that some other serotonergic genes are associated with diurnal preference.…”
mentioning
confidence: 99%
“…This study was conducted following the Declaration of Helsinki. Other findings involving these study subjects have been previously reported [25,[28][29][30][31][32][33].…”
Section: Subjectssupporting
confidence: 78%
“…Other genes that were not the clock were also related to chronotype and psychiatric disorders. A study found that a candidate for Serotonin 2A receptor gene (5HT2A) receptor (HTR2A), which is located on chromosome 13q14-q21, was associated with mental (depression, schizophrenia) and behavioral (suicidal and aggressive behaviors) disorders and was associated with chronotype in a healthy population ( Yeom et al, 2020 ). Additionally, GWAS of the UK Biobank also indicated HTR6 rs2050122 was related to chronotype.…”
Section: The Differences Between Chronotypes and The Association With...mentioning
confidence: 99%